High-purity hastelloy c-276 ultra-thin base strip and preparation method thereof

CN122918364APending Publication Date: 2026-10-16NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611102776.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

第一、对铸锭纯净度的控制不够精细

Benefits of technology

(1)高纯净度。本发明采用真空感应熔炼+电渣重熔+真空自耗重熔的三联熔炼工艺,通过真空感应熔炼实现合金成分的精准控制和初步纯净化,通过电渣重熔进一步去除硫、磷等杂质元素和非金属夹杂物,通过真空自耗重熔实现组织的均匀化和致密化。三重纯化手段协同作用,将杂质元素和夹杂物含量控制在极低水平,从源头上保证了基带的加工性能和表面质量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a high-purity Hastelloy C-276 extremely thin base strip and a preparation method thereof, and comprises the following steps: (1) vacuum induction melting of raw materials; (2) electroslag remelting of alloy blank; (3) vacuum consumable remelting of remelted blank; (4) rough rolling of alloy ingot; (5) intermediate rolling of rough-rolled slab; (6) finish rolling of intermediate-rolled slab; (7) final annealing of alloy plate; and (8) surface modification of alloy plate. The application can effectively solve the technical problems of insufficient purity of the ingot, low efficiency of work hardening elimination, lack of systematic control of magnetic permeability and inability of the surface flatness to meet the requirements of the IBAD preparation route in the preparation process of the existing Hastelloy base strip, and successfully prepares the Hastelloy C-276 extremely thin base strip with high purity, ultra-low magnetic permeability and atomic-level surface flatness, which can meet the preparation requirements of high-temperature superconducting tapes in strong magnetic field scenarios such as fusion devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy material processing technology, and in particular to a high-purity Hastelloy C-276 ultrathin substrate and its preparation method. Background Technology

[0002] Hastelloy C-276 is a nickel-based superalloy chosen as the preferred metal substrate material for second-generation high-temperature superconducting tapes (REBCO) due to its excellent mechanical properties, good corrosion resistance, and extremely low magnetic properties. REBCO tapes are considered the core material for "super magnets" in controlled nuclear fusion, and their metal substrates are primarily made of Hastelloy C-276. Depending on the application requirements, the thickness of Hastelloy C-276 substrates needs to be within approximately 50 μm. However, this superalloy exhibits a significant work hardening tendency, posing considerable challenges to the rolling process of ultra-thin tapes.

[0003] Currently, although some domestic companies have achieved the back-end preparation of high-temperature superconducting tapes, the precision baseband of Hastelloy C-276 still mainly relies on imports due to the limitations of Hastelloy's ultra-thin precision rolling technology. The high price and unreliable supply cycle severely restrict the improvement of the high-temperature superconducting industry chain and the localization process.

[0004] Methods for preparing Hastelloy C-276 precision base strips have been reported in the prior art. For example, patent CN117488118B discloses a preparation method that sequentially involves ingot melting, forging and raw material forming, first rolling stroke, second rolling stroke, tension leveling, finished product rolling, cleaning, and polishing to obtain the base strip. However, the prior art still has the following shortcomings: First, the control over the purity of the ingot is not precise enough. Existing smelting processes have limited ability to remove impurity elements and non-metallic inclusions. High impurity content not only affects the surface quality of the subsequent rolling process, but also has an adverse effect on the epitaxial growth of the superconducting film. Secondly, the efficiency of eliminating work hardening needs to be improved. Hastelloy C-276 has a significant tendency to work harden, and existing processes often require a large number of rolling passes and intermediate annealing cycles, resulting in low production efficiency. Furthermore, the annealing process parameters lack systematic optimization. Third, there is a lack of systematic control technology for baseband permeability. Existing technologies mainly rely on the weak magnetic characteristics of Hastelloy C-276 material itself, without fully considering the influence of factors such as stress state and microstructure evolution during processing on magnetic properties. This results in large fluctuations in the permeability of the finished product, making it difficult to meet the stringent requirements of strong magnetic field scenarios such as fusion devices. Fourth, surface roughness control has not yet reached the atomic-level flatness requirements of the ion beam assisted deposition (IBAD) technology route. The IBAD route requires a baseband surface roughness Ra ≤ 2nm (5μm × 5μm), but existing technologies struggle to consistently achieve this standard. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose a high-purity Hastelloy C-276 ultrathin substrate and its preparation method.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a high-purity Hastelloy C-276 ultrathin substrate, comprising the following steps: (1) The Hastelloy C-276 raw material was subjected to triple melting to obtain alloy ingots; (2) The alloy ingot is forged and hot-rolled to obtain a hot-rolled slab; (3) The hot-rolled slab is subjected to a first cold rolling process, with the total deformation controlled at 45% to 55%, and water bath cooling is used; (4) The strip that has undergone the first cold rolling is subjected to a second cold rolling, the second cold rolling includes multiple sub-rolling passes, each sub-rolling pass includes annealing and cold rolling processes performed sequentially, and the total deformation of the second cold rolling is 75%~85%; (5) Perform magnetic testing on the strip that has undergone the second cold rolling; (6) For strips that pass the magnetic test, a third cold rolling process is carried out, using mirror rolls for finishing rolling, and the total deformation is controlled to be 50%~65%; (7) Perform final vacuum annealing on the strip that has undergone the third cold rolling; (8) Electrochemical polishing of the strip after final vacuum annealing; (9) Deposition of amorphous oxide thin films on the electrochemically polished strip.

[0007] Furthermore, the triple melting process in step (1) consists of vacuum induction melting, electroslag remelting, and vacuum consumable remelting, in sequence; the vacuum degree of the vacuum induction melting is ≤1.0×10⁻⁶. -2 The refining temperature is 1480~1520℃, and the holding time is 60~90min; the electroslag remelting adopts a CaF2-CaO-Al2O3 ternary slag system, with a basicity of 1.8~2.5 and a current density of 3000~5000A / m. 2 The melting rate is 2~5 kg / min; the vacuum degree of the vacuum self-consumable remelting is ≤1.0×10⁻⁶. -1 Pa, melting rate is 1~3 kg / min.

[0008] Furthermore, in step (3), the first cold rolling is carried out in 3 to 6 passes, and the deformation amount of each pass is 8% to 15%.

[0009] Furthermore, in step (4), the second cold rolling includes 3 to 6 sub-rolling passes, and the deformation of each sub-rolling pass is 15% to 25%; the annealing treatment is carried out under vacuum conditions, and water bath cooling is used after annealing.

[0010] Furthermore, the standard for magnetic detection in step (5) is: the specific magnetic moment of the strip ≤ 1.5 × 10⁻⁶. -5 emu / g.

[0011] Furthermore, in step (6), the deformation amount of each pass of the third cold rolling is 3% to 7%.

[0012] Furthermore, the final vacuum annealing in step (7) is carried out in a vacuum or pure hydrogen protective atmosphere, with an annealing temperature of 1050~1100℃ and a holding time of 10~20min; the magnetic permeability of the strip after annealing is ≤1.0003.

[0013] Furthermore, the electrochemical polishing process conditions in step (8) are: current density 0.3~0.8 A / cm². 2 The voltage is 10~15V, the processing time is 30~120s, the electrolyte is a phosphoric acid-sulfuric acid system with a volume ratio of 3:1~4:1, and the electrolyte temperature is 50~70℃.

[0014] Furthermore, the amorphous oxide film in step (9) is an Al2O3 film or a Y2O3 film, deposited by chemical solution deposition, with a concentration of 0.1~0.5mol / L for the deposition solution, and after deposition, it is heat-treated at 600~800℃ for 30~60min, and the thickness of the amorphous oxide film is 5~20nm.

[0015] Secondly, the present invention provides a Hastelloy C-276 ultrathin substrate prepared by any of the above preparation methods, wherein the ultrathin substrate has a thickness of 0.035~0.045mm, a magnetic permeability ≤1.0003, and a surface roughness Ra≤2nm.

[0016] The advantages and positive effects of this invention are as follows: (1) High purity. This invention employs a triple smelting process of vacuum induction melting, electroslag remelting, and vacuum consumable remelting. Vacuum induction melting achieves precise control and preliminary purification of the alloy composition, electroslag remelting further removes impurities such as sulfur and phosphorus and non-metallic inclusions, and vacuum consumable remelting achieves homogenization and densification of the microstructure. The synergistic effect of these three purification methods controls the content of impurities and inclusions to extremely low levels, ensuring the processing performance and surface quality of the substrate from the source.

[0017] (2) Efficient elimination of work hardening. This invention optimizes the design of a three-stage cold rolling process—first cold rolling (total deformation 45%~55%), second cold rolling (total deformation 75%~85%, divided into 3~6 sub-rolling passes, each sub-rolling pass is followed by vacuum annealing), and third cold rolling (total deformation 50%~65%, mirror finish rolling)—combining the deformation distribution and annealing regime optimization of each stage, thereby achieving efficient step-by-step elimination of work hardening, reducing the total number of rolling passes and annealing times, and improving production efficiency.

[0018] (3) Ultra-low magnetic permeability. This invention includes an intermediate magnetic detection process after the second cold rolling, to achieve a specific magnetic moment ≤ 1.5 × 10⁻⁶. -5 Using emu / g as a screening standard ensures that the strip entering the finishing rolling stage has excellent basic magnetic properties. Combined with the final vacuum annealing process (1050~1100℃, 10~20min) to regulate the permeability, the finished product's permeability is stably controlled at ≤1.0003. This systematic magnetic property control strategy ensures the applicability of the baseband in strong magnetic field environments such as fusion devices.

[0019] (4) Atomic-level surface smoothness. This invention employs a composite surface modification process combining electrochemical polishing and chemical solution deposition of amorphous oxide thin films. Electrochemical polishing utilizes electrochemical dissolution to rapidly remove microscopic protrusions and processed altered layers from the surface, reducing surface roughness to a low level. Subsequently, a 5-20 nm amorphous Al2O3 or Y2O3 thin film is deposited on the substrate surface via chemical solution deposition to further fill microscopic defects and smooth the surface. The synergistic effect of these two processes results in a final surface roughness of Ra≤2nm (5μm×5μm), meeting the stringent requirements for substrate surface smoothness in the IBAD technology route.

[0020] (5) Excellent comprehensive performance. The Hastelloy C-276 ultrathin substrate prepared by the method of the present invention has a thickness of 0.035~0.045mm, and has high purity, ultra-low magnetic permeability and atomic-level surface flatness, which can meet the preparation requirements of second-generation high-temperature superconducting tapes in strong magnetic field scenarios such as fusion devices. Detailed Implementation

[0021] The present invention will now be described in further detail. The basic structure of the invention is illustrated only by way of illustration, and therefore only the components relevant to the invention are shown.

[0022] Example 1

[0023] This embodiment provides a method for preparing an ultrathin Hastelloy C-276 substrate, the specific steps of which are as follows: (1) Preparation of ingots by triple smelting The charge was prepared according to the following proportions: Cr: 15.5%, Fe: 5.5%, Mo: 16.0%, W: 3.8%, and Ni as the balance. First, vacuum induction melting was performed at a vacuum degree of 1.0 × 10⁻⁶. -2 The refining temperature was 1500℃, and the holding time was 80 min. The resulting billet was then subjected to electroslag remelting using a CaF2-CaO-Al2O3 ternary slag system at a basicity of 2.0 and a current density of 4000 A / m³. 2 The melting rate was 3 kg / min. Finally, the electroslag remelted billet was subjected to vacuum arc remelting at a vacuum degree of 1.0 × 10⁻⁶. -1 Pa, with a melting rate of 2 kg / min, yields an alloy ingot.

[0024] (2) Forging and hot rolling The obtained alloy ingot was forged and hot-rolled at 1150℃ to obtain a hot-rolled slab.

[0025] (3) First cold rolling The hot-rolled slab is subjected to a first cold rolling process with a total deformation of 50%, which is carried out in 5 passes, with a deformation of 10% to 12% in each pass, and water bath cooling is used.

[0026] (4) Second cold rolling The strip that has undergone the first cold rolling process is then subjected to a second cold rolling process, which consists of four sub-passes. Each sub-pass includes sequential vacuum annealing and cold rolling. The deformation amount of each sub-pass is 18% to 22%, and the total deformation amount of the second cold rolling is 80%. The annealing temperatures for each sub-pass are 1120℃, 1100℃, 1080℃, and 1060℃, respectively, with an annealing time of 10 minutes. After annealing, the strip is cooled in a water bath.

[0027] (5) Intermediate magnetic detection Magnetic testing was performed on the strip after the second cold rolling, and the specific magnetic moment was measured to be 1.2 × 10⁻⁶. -5 emu / g, conforming to ≤1.5×10 -5 The standard requirements of emu / g.

[0028] (6) Third cold rolling The strip that passes the magnetic test is subjected to a third cold rolling process with a total deformation of 55% and a deformation of 5% to 6% per pass. Mirror-finish rolls are used for finishing rolling.

[0029] (7) Final vacuum annealing The strip that has undergone the third cold rolling process is then subjected to final vacuum annealing at a vacuum level of 5×10⁻⁶. -3 Pa, annealing temperature is 1080℃, holding time is 15min.

[0030] (8) Electrochemical polishing The strip after final vacuum annealing was subjected to electrochemical polishing at a current density of 0.5 A / cm². 2 The voltage was 12V, the processing time was 60s, the electrolyte was a phosphoric acid-sulfuric acid system with a volume ratio of 3:1, and the electrolyte temperature was 60℃.

[0031] (9) Deposition of amorphous oxide thin films Amorphous Al2O3 thin films were deposited by chemical solution deposition on the electrochemically polished strip at a solution concentration of 0.3 mol / L. After deposition, the films were heat-treated at 700 °C for 45 min, and the film thickness was approximately 10 nm.

[0032] The Hastelloy C-276 ultrathin substrate prepared in this embodiment has a thickness of 0.040 mm, a width of 12 mm, a surface roughness Ra=1.8 nm (5 μm × 5 μm), a magnetic permeability of 1.0002, a tensile strength of 1920 MPa at 77 K, and a room temperature tensile strength of 1250 MPa after heat treatment at 900 °C for 5 min.

[0033] The difference between Comparative Example 1 and Example 1 is that the electroslag remelting step is omitted, and vacuum arc remelting is performed directly after vacuum induction melting. The specific steps are as follows: (1) The same proportions as in Example 1 were used for vacuum induction melting, and the process parameters were the same as in Example 1.

[0034] (2) The billet obtained by melting is directly subjected to vacuum self-consumption remelting, and the process parameters are the same as in Example 1.

[0035] (3) to (9) The subsequent steps are the same as in Example 1.

[0036] Testing revealed that the sulfur content of the Hastelloy C-276 ultrathin substrate prepared in this comparative example was 0.002%, the inclusion rating was D (fine) grade 2.0, microcracks appeared on the surface, and the yield was about 30% lower than that of Example 1.

[0037] Comparative Example 1 shows that omitting the electroslag remelting step significantly reduces the purity of the alloy, increases the sulfur content and inclusion levels, leading to microcracks on the surface during subsequent rolling and a substantial decrease in yield. This verifies the important role of electroslag remelting in improving the purity of ingots.

[0038] The difference between Comparative Example 2 and Example 1 is that the intermediate magnetic detection in step (5) and the final vacuum annealing in step (7) are omitted. The specific steps are as follows: (1)~(4) are the same as in Example 1.

[0039] (5) The strip that has undergone the second cold rolling is directly subjected to the third cold rolling (same as step (6) in Example 1).

[0040] (6) The strip that has undergone the third cold rolling is directly electrochemically polished (same as step (8) in Example 1).

[0041] (7) Deposit amorphous oxide thin film on the electrochemically polished strip (same as step (9) in Example 1).

[0042] Testing revealed that the Hastelloy C-276 ultrathin substrate prepared in this comparative example has a permeability of 1.0008 and a specific magnetic moment of 3.5 × 10⁻⁶. -5 The emu / g ratio cannot meet the application requirements of fusion devices for a baseband permeability of ≤1.0003.

[0043] Comparative Example 2 shows that after omitting intermediate magnetic detection and final vacuum annealing, the permeability of the baseband increases significantly, exceeding the usage requirements of strong magnetic field scenarios such as fusion devices. This verifies the effectiveness of the systematic magnetic performance control strategy that combines intermediate magnetic detection screening with final vacuum annealing regulation.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that the electrochemical polishing step was omitted, and amorphous oxide thin film deposition was performed directly after final vacuum annealing. The specific steps are as follows: (1)~(7) are the same as in Example 1.

[0045] (8) Chemical solution deposition of amorphous Al2O3 thin film is performed directly on the strip after final vacuum annealing (same as step (9) in Example 1).

[0046] Testing revealed that the surface roughness Ra of the Hastelloy C-276 ultrathin substrate prepared in this comparative example was approximately 5~8 nm (5 μm × 5 μm), which is higher than the requirement of Ra ≤ 2 nm for the substrate surface roughness in the IBAD technical route.

[0047] Comparative Example 3 shows that, without electrochemical polishing, amorphous oxide film deposition alone cannot reduce the surface roughness to the atomic level of smoothness required by the IBAD route, thus verifying the necessity of the composite surface modification process of electrochemical polishing + amorphous oxide film deposition.

[0048] Performance Comparison The key performance indicators of the Hastelloy C-276 ultrathin substrate obtained in Example 1 and the comparative examples are listed in Table 1: Table 1 Performance Comparison of Examples and Comparative Examples

[0049] As shown in Table 1, only the Hastelloy C-276 ultrathin substrate prepared in Example 1 of this invention simultaneously meets all the requirements of high purity, ultra-low magnetic permeability (≤1.0003), and atomic-level surface smoothness (Ra≤2nm), which can meet the preparation requirements of second-generation high-temperature superconducting tapes in strong magnetic field scenarios such as IBAD technology routes and fusion devices. The Hastelloy C-276 ultrathin substrate obtained in Example 1 has controllable thickness, smooth surface, low magnetic permeability, and high tensile strength. The Hastelloy C-276 ultrathin substrate obtained in Comparative Example 1 has high sulfur content, rough surface, microcracks, and low yield. The Hastelloy C-276 ultrathin substrate obtained in Comparative Example 2 has high magnetic permeability, which cannot meet the application requirements of fusion devices.

[0050] Industrial applicability

[0051] The method for preparing Hastelloy C-276 ultrathin substrate provided by this invention has a complete process route, is highly operable, and is suitable for industrial mass production. The ultrathin substrate prepared using this method can be widely used in the manufacture of second-generation high-temperature superconducting tapes, especially for high-temperature superconducting tapes for applications in strong magnetic fields such as controlled nuclear fusion devices, and has good market prospects and industrialization value.

[0052] The advantages and positive effects of this invention are as follows: (1) High purity. This invention employs a triple smelting process of vacuum induction melting, electroslag remelting, and vacuum consumable remelting. Vacuum induction melting achieves precise control and preliminary purification of the alloy composition, electroslag remelting further removes impurities such as sulfur and phosphorus and non-metallic inclusions, and vacuum consumable remelting achieves homogenization and densification of the microstructure. The synergistic effect of these three purification methods controls the content of impurities and inclusions to extremely low levels, ensuring the processing performance and surface quality of the substrate from the source.

[0053] (2) Efficient elimination of work hardening. This invention optimizes the design of a three-stage cold rolling process—first cold rolling (total deformation 45%~55%), second cold rolling (total deformation 75%~85%, divided into 3~6 sub-rolling passes, each sub-rolling pass is followed by vacuum annealing), and third cold rolling (total deformation 50%~65%, mirror finish rolling)—combining the deformation distribution and annealing regime optimization of each stage, thereby achieving efficient step-by-step elimination of work hardening, reducing the total number of rolling passes and annealing times, and improving production efficiency.

[0054] (3) Ultra-low magnetic permeability. This invention includes an intermediate magnetic detection process after the second cold rolling, to achieve a specific magnetic moment ≤ 1.5 × 10⁻⁶. -5Using emu / g as a screening standard ensures that the strip entering the finishing rolling stage has excellent basic magnetic properties. Combined with the final vacuum annealing process (1050~1100℃, 10~20min) to regulate the permeability, the finished product's permeability is stably controlled at ≤1.0003. This systematic magnetic property control strategy ensures the applicability of the baseband in strong magnetic field environments such as fusion devices.

[0055] (4) Atomic-level surface smoothness. This invention employs a composite surface modification process combining electrochemical polishing and chemical solution deposition of amorphous oxide thin films. Electrochemical polishing utilizes electrochemical dissolution to rapidly remove microscopic protrusions and processed altered layers from the surface, reducing surface roughness to a low level. Subsequently, a 5-20 nm amorphous Al2O3 or Y2O3 thin film is deposited on the substrate surface via chemical solution deposition to further fill microscopic defects and smooth the surface. The synergistic effect of these two processes results in a final surface roughness of Ra≤2nm (5μm×5μm), meeting the stringent requirements for substrate surface smoothness in the IBAD technology route.

[0056] (5) Excellent comprehensive performance. The Hastelloy C-276 ultrathin substrate prepared by the method of the present invention has a thickness of 0.035~0.045mm, and has high purity, ultra-low magnetic permeability and atomic-level surface flatness, which can meet the preparation requirements of second-generation high-temperature superconducting tapes in strong magnetic field scenarios such as fusion devices.

[0057] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or equivalent variations to the disclosed technical content and apply them to other fields. However, any simple modifications, equivalent variations, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention. For those skilled in the art, the specific meaning of the above terms in the present invention can be understood through specific circumstances.

Claims

1. A method for preparing a high-purity Hastelloy C-276 ultrathin substrate, characterized in that, Includes the following steps: (1) The Hastelloy C-276 raw material was subjected to triple melting to obtain alloy ingots; (2) The alloy ingot is forged and hot-rolled to obtain a hot-rolled slab; (3) The hot-rolled slab is subjected to a first cold rolling process, with the total deformation controlled at 45% to 55%, and water bath cooling is used; (4) The strip that has undergone the first cold rolling is subjected to a second cold rolling, the second cold rolling includes multiple sub-rolling passes, each sub-rolling pass includes annealing and cold rolling processes performed sequentially, and the total deformation of the second cold rolling is 75%~85%; (5) Perform magnetic testing on the strip that has undergone the second cold rolling; (6) For strips that pass the magnetic test, a third cold rolling process is carried out, using mirror rolls for finishing rolling, and the total deformation is controlled to be 50%~65%; (7) Perform final vacuum annealing on the strip that has undergone the third cold rolling; (8) Electrochemical polishing of the strip after final vacuum annealing; (9) Amorphous oxide thin film deposition is performed on the electrochemically polished strip.

2. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 1, characterized in that, The three-stage melting process in step (1) consists of vacuum induction melting, electroslag remelting, and vacuum consumable remelting, in sequence; the vacuum degree of the vacuum induction melting is ≤1.0×10⁻⁶. -2 The refining temperature is 1480~1520℃, and the holding time is 60~90min; the electroslag remelting adopts a CaF2-CaO-Al2O3 ternary slag system, with a basicity of 1.8~2.5 and a current density of 3000~5000A / m. 2 The melting rate is 2~5 kg / min; the vacuum degree of the vacuum self-consumable remelting is ≤1.0×10⁻⁶. -1 Pa, melting rate is 1~3 kg / min.

3. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 2, characterized in that, In step (3), the first cold rolling is carried out in 3 to 6 passes, and the deformation amount of each pass is 8% to 15%.

4. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 3, characterized in that, In step (4), the second cold rolling includes 3 to 6 sub-rolling passes, and the deformation of each sub-rolling pass is 15% to 25%; the annealing treatment is carried out under vacuum conditions, and water bath cooling is used after annealing.

5. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 4, characterized in that, The standard for magnetic detection in step (5) is: the specific magnetic moment of the strip ≤ 1.5 × 10⁻⁶. -5 emu / g.

6. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 5, characterized in that, In step (6), the deformation amount of each pass of the third cold rolling is 3% to 7%.

7. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 6, characterized in that, The final vacuum annealing in step (7) is carried out in a vacuum or pure hydrogen protective atmosphere, with an annealing temperature of 1050~1100℃ and a holding time of 10~20min; the magnetic permeability of the strip after annealing is ≤1.0003.

8. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 7, characterized in that, The electrochemical polishing process conditions in step (8) are: current density 0.3~0.8 A / cm². 2 The voltage is 10~15V, the processing time is 30~120s, the electrolyte is a phosphoric acid-sulfuric acid system with a volume ratio of 3:1~4:1, and the electrolyte temperature is 50~70℃.

9. The method for preparing high-purity Hastelloy C-276 ultrathin substrate according to claim 8, characterized in that, The amorphous oxide film in step (9) is an Al2O3 film or a Y2O3 film, deposited by chemical solution deposition. The concentration of the deposition solution is 0.1~0.5mol / L. After deposition, it is heat-treated at 600~800℃ for 30~60min. The thickness of the amorphous oxide film is 5~20nm.

10. A Hastelloy C-276 ultrathin substrate prepared by the preparation method according to any one of claims 1 to 9, characterized in that, The ultrathin baseband has a thickness of 0.035~0.045mm, a magnetic permeability of ≤1.0003, and a surface roughness Ra≤2nm.